Collective health teaching: the construction of academic knowledge and practices (Research, Society and Development, 2020)
This study aims to share an experience report on the teaching structure in a Public Health discipline. It is an experience report and documentary analysis, with a qualitative, descriptive and exploratory approach, with 45 participants, being students regularly enrolled in a Collective Health discipline. Data collection occurred through the application of a questionnaire to the participants, as well as the documentary analysis of the menu of that discipline. The data were analyzed using Bardin's Content Analysis approximations (2016) producing the categories presented. For this study, the ethical criteria for research with human beings were also observed. The results verified the disciplinary consistency in relation to the objective, skills and competences, methodology and evaluation that make up the discipline. The research carried out also made it possible to analyze the students' perception of the disciplinary experience, with emphasis on the didactics employed and the evaluation model constructed jointly by the teacher with the class. Thus, evaluating the disciplinary construction and the academic practice performed becomes important to qualify the learning offered to academic and professional training.